PENINGKATAN DAYA SAING UMKM MELALUI PEMANFAATAN APLIKASI PEMBUKUAN BERBASIS ANDROID - Fathimatus Zahro Fazda Oktavia; Yunia Afiatin; Dyah Metha Nurftriasih; Rika Wijayanti; Farisa Nur Maula (Jurnal Pengabdian kepada Masyarakat, 2023)
The Pelangi Nusantara (PELANUSA) social entrepreneur community is a fairly large MSME community with the number of groups reaching 21 groups spread across Java to East Nusa Tenggara. So far, the PELANUSA community has grown tremendously with sales reach both domestically and abroad. However, there are several things that the community wants to continue to develop, one of which is digitalization in the financial sector. Therefore, this service activity aims to increase the competitiveness of MSMEs, especially members of the PELANUSA community, through the use of an Android-based bookkeeping application, namely BukuWarung. Concrete steps that will be taken are introducing simple financial bookkeeping, introducing the BukuWarung, teaching and training members to do bookkeeping through the BukuWarung. The results of the evaluation after the training showed that the training materials were considered to provide solutions to the problems being faced, experienced an increase in independence or skills, and felt satisfaction with the PPM activities that had been carried out.